A hydrodynamic and thermodinamic gravity reduced coastal model. A study case: Pisco and Paracas bays - Carbonel, C.A. A. (2013)
A reduced gravity non-linear model is proposed to describe the hydrodynamic behaviour and thermodynamic of a coastal systems including areas with shallow depths. The model is approached using a finite difference formulation in a domain with open boundary conditions describing the behaviour of a surface layer on an inert substrate layer conserving in this way the low frequency dynamic. The Pisco and Paracas bays is the study area which is characterized by the presence of hydrodynamic convergences and divergences producing changes in the temperature field of the region. First, numerical experiments are developed for permanent cases considering representative winds distributions. Later, a non-permanent case is simulated and the time dependent model solutions are compared with spatial observations.